1999
DOI: 10.1093/humrep/14.4.928
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Laparoscopically assisted full thickness skin graft for reconstruction in congenital agenesis of vagina and uterine cervix

Abstract: In patients with agenesis of the vagina and cervix but with a functional endometrium, the traditional treatment is hysterectomy with construction of a neovagina. We report successful treatment by laparoscopically assisted full thickness skin graft for reconstruction in a patient with congenital agenesis of the vagina and uterine cervix concomitant with haematometra and ovarian endometrioma in a 12 year old girl. Postoperatively, the vaginal skin graft healed well, and menstruation first appeared 4 weeks later.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…A successful laparoscopic treatment of the agenesis of vagina and uterine cervix has been reported in which the neovagina was created with the McIndoe technique (14). However, earlier studies have shown that neovagina created with skin grafts maintain a keratinized epithelium with sebaceous glands and hairs many years after the operation (15).…”
Section: Discussionmentioning
confidence: 99%
“…A successful laparoscopic treatment of the agenesis of vagina and uterine cervix has been reported in which the neovagina was created with the McIndoe technique (14). However, earlier studies have shown that neovagina created with skin grafts maintain a keratinized epithelium with sebaceous glands and hairs many years after the operation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Exposed raw surfaces would form granulation tissues, scarring, and eventually cause restenosis of the anastomosis. [2] The use of autologous tissues for reconstruction is the first choice in most patients, but the use of soft tissues alone in this patient-such as a skin graft, local flap, or free tissue transfer-would likely become functionally obstructed due to the high contractile forces of the uterine musculature.…”
Section: Case Reportmentioning
confidence: 99%
“…More recently, new methods for reconstruction of cervical and vaginal agenesis, including full-thickness skin grafts, prefabricated bilateral pudendal thigh flaps, and free microvascular transfer of the appendix and ascending colon, have resulted in good outcomes (2,5,7). However, they have their disadvantages.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations